2017
DOI: 10.3390/vetsci4040054
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility Is Similar between Commercial Diets That Provide Ingredients with Different Perceived Glycemic Responses and the Inaccuracy of Using the Modified Atwater Calculation to Calculate Metabolizable Energy

Abstract: Dietary starch is required for a dry, extruded kibble; the most common diet type for domesticated felines in North America. However, the amount and source of dietary starch may affect digestibility and metabolism of other macronutrients. The objectives of this study were to evaluate the effects of 3 commercial cat diets on in vivo and in vitro energy and macronutrient digestibility, and to analyze the accuracy of the modified Atwater equation. Dietary treatments differed in their perceived glycemic response (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Those estimates led to the use of modified Atwater factors (3.5, 8.5, and 3.5 kcal/g for protein, fat, and digestible carbohydrate, respectively). Although those values provide a better estimate of ME for pet foods than do the Atwater factors, they underestimate the energy content of highly digestible foods, including today’s premium or super-premium diets ( Laflamme, 2001 ; Asaro et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those estimates led to the use of modified Atwater factors (3.5, 8.5, and 3.5 kcal/g for protein, fat, and digestible carbohydrate, respectively). Although those values provide a better estimate of ME for pet foods than do the Atwater factors, they underestimate the energy content of highly digestible foods, including today’s premium or super-premium diets ( Laflamme, 2001 ; Asaro et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that differences in carbohydrate content and resulting intake of the experimental diets in the present study stimulate variable lipid synthesis, and therefore different postprandial EE among treatments. Furthermore, we previously determined that the calculated ME from which feeding recommendations were developed was inaccurate (Asaro et al, 2017). When caloric intake was reanalyzed using the true ME of the diets, we found that cats were unintentionally offered nonisocaloric provisions, with more energy being consumed by cats fed the high PGR diet (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cats were fed to maintain BW using individual historical data of energy intake. Dietary ME was calculated using the modified Atwater calculation, though it was later determined that the Atwater equation consistently underestimated true ME of the experimental diets (AAFCO, 1997;Asaro et al, 2017). Cats followed an 8-d prefeeding schedule followed by calorimetry and glucose measures.…”
Section: Animals Diets and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations